Composite material, separator, battery and electric device
By using composite materials including metal organic framework compounds and chelates in battery isolation films, the problems of poor battery reliability and cycle performance are solved, and the effects of increasing battery reversible capacity and reducing self-discharge rate are achieved.
Patent Information
- Application Number
- CN202310904962.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-07-21
AI Technical Summary
When existing battery isolation membranes are applied to batteries, the battery's usage reliability and cycling performance are still poor.
An isolation film including a base material and a functional layer is used. The functional layer is composed of a composite material. The composite material includes a metal organic framework compound and a chelate connected to each other. The metal organic framework compound is formed by coordination of metal ions and organic ligands. The metal ion has a valence of more than two, and the organic ligand includes a polycarboxylic acid group.
Through the pore size effect and electrostatic synergistic binding of metal organic framework materials, and the chelation effect of chelates, the content of metal impurity ions in the electrolyte is reduced, the number of metal impurity ions migrating to the negative electrode sheet is reduced, and the reversible capacity and use of the battery are improved. reliability and reduce self-discharge rate.
Smart Images

Figure CN119340609A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a composite material, an isolation film, a battery and an electrical device. Background Art
[0002] Batteries have the characteristics of high capacity and long life, so they are widely used in electronic devices such as mobile phones, laptops, battery cars, electric cars, electric airplanes, electric ships, electric toy cars, electric toy ships, electric toy airplanes and electric tools, etc. As batteries have made great progress, higher requirements are placed on battery performance. In order to improve the performance of battery cells, the isolation membrane in the battery is usually optimized and improved.
[0003] However, currently when the separator is applied to batteries, the battery reliability and cycle performance are still poor. Summary of the invention
[0004] The present application provides a composite material, a separator, a battery and an electrical device. The use reliability and cycle performance of the battery described in the present application can be improved.
[0005] In a first aspect, an embodiment of the present application proposes an isolation membrane, which includes a substrate and a functional layer arranged on at least one side of the substrate, the functional layer includes a composite material, the composite material includes a metal-organic framework compound and a chelate connected to each other, the metal-organic framework compound is formed by coordination of metal ions and organic ligands, the valence of the metal ions is greater than or equal to divalence, and the organic ligands include polycarboxylic acid groups.
[0006] Therefore, in the embodiment of the present application, the isolation membrane includes a composite material, and the composite material includes a metal organic framework compound and a chelate connected to each other, and the metal organic framework compound is formed by the coordination of metal ions and organic ligands, the valence of the metal ions is divalent or more, and the organic ligands include a polycarboxylic acid structure. When the isolation membrane is applied to a battery cell, the metal organic framework material can bind metal impurity ions through pore size and electrostatic synergy, and the chelate can further bind to the metal impurity ions through chelation, reducing the content of metal impurity ions in the electrolyte, thereby reducing the number of metal impurity ions migrating to the negative electrode plate, increasing the position of active ions embedded in the negative electrode plate, and improving the reversible capacity of the battery cell; and reducing the risk of metal impurity ions precipitating on the surface of the negative electrode plate to form metal dendrites, improving the reliability of the battery cell; thereby, the self-discharge rate of the battery cell can be reduced, and the cycle performance of the battery cell can be improved.
[0007] In some embodiments, the valence of the metal ion is greater than or equal to tetravalence; alternatively, the valence of the metal ion is greater than or equal to pentavalence; further alternatively, the valence of the metal ion is greater than or equal to hexavalence. As the valence of the metal ion increases, the number of connection sites that the metal ion can provide increases, that is, the number of organic ligands coordinated to the metal ion increases, which is conducive to the formation of a metal organic framework compound with a smaller pore size, and is conducive to the metal organic framework compound adsorbing metal impurity ions through the pore size effect.
[0008] In some embodiments, the metal ions may include Zr 2+ 、Zr 3+ 、Zr 4+ 、Bi 3+ 、Bi 5+ 、Zn 2+ , Hf 4+ 、Co 2+ 、Co 3+ , Mn 4+ , Mn 5+ and Mn 6+ At least one of; Optionally, the metal ion may include Zr 3+ 、Zr 4+ 、Bi 3+ 、Bi 5+ , Hf 4+ 、Co 3+ , Mn 4+ , Mn 5+ and Mn 6+ At least one of; further optionally, the metal ions may include Zr 4+ 、Bi 5+ , Hf 4+ , Mn 4+ , Mn 5+ and Mn 6+ At least one of; Further optionally, the metal ions may include Bi 5+ , Mn 5+ and Mn 6+ At least one of; Further optionally, the metal ions may include Mn 6+ .
[0009] In some embodiments, the organic ligand includes at least one of phthalic acid, terephthalic acid, 1,4-cyclohexanedicarboxylic acid, isophthalic acid, 4,4'-sulfonyl dibenzoic acid and 4,4'-dicarboxyl diphenyl ether. The above materials can exist stably for a long time in organic solvents, and because they all have a polycarboxylic acid structure, they are conducive to combining with chelates to improve the structural stability of the composite material.
[0010] In some embodiments, the chelate includes at least one of a carboxylic acid group, a phosphonic acid group and octanoyl hydroxamic acid; optionally, the chelate containing the carboxylic acid group includes at least one of ethylenediaminetetraacetic acid, aminotriacetic acid, diethylenetriaminepentaacetic acid and diethylenetriaminepentatriacetic acid; optionally, the chelate containing the phosphonic acid group includes one or more of hydroxyethylidene-1,1-diphosphonic acid, aminotrimethylenephosphonic acid, diethylenetriaminepentamethylenephosphonic acid, triethylenetetraaminehexamethylenphosphonic acid, bis(1,6-hexyl)triaminepentamethylenephosphonic acid and polyaminopolyethertetramethylenphosphonic acid. The coordination effect between the above chelate and the metal impurity ions is stronger, which is conducive to stabilizing the metal impurity ions in the isolation membrane. Moreover, the above chelate has good compatibility with the organic solvent in the electrolyte, which can improve the wetting performance of the electrolyte on the isolation membrane.
[0011] In some embodiments, the volume average particle size Dv50 of the composite material is 100 nm to 300 nm; and / or the average pore size of the composite material is 0.50 nm to 1.10 nm. When the average pore size of the composite material is within the above range, the average pore size of the composite material is relatively small, which is conducive to the composite material to play the role of pore size and adsorb metal impurity ions in the pore structure of the composite material.
[0012] In some embodiments, based on the mass of the composite material, the ratio of the mass percentage of the chelate to the mass percentage of the metal organic framework compound is 0.01 to 0.10: 1. When the mass percentage ratio of the chelate to the metal organic framework compound is within the above range, the metal organic framework compound plays a major role in adsorbing metal impurity ions, and the chelate plays an auxiliary role in chelating metal impurity ions. The two work together to stabilize the metal impurity ions in the composite material, which can effectively reduce the content of metal impurity ions in the system.
[0013] In some embodiments, based on the mass of the functional layer, the mass percentage of the composite material is 0.1% to 1.0%. When the mass percentage of the composite material is within the above range, the metal impurity ions in the battery monomer system can be effectively adsorbed and stabilized.
[0014] In some embodiments, the functional layer further includes heat-resistant particles; optionally, the mass percentage of the heat-resistant particles in the functional layer is less than or equal to 50%, and the heat-resistant particles can improve the heat resistance of the isolation film.
[0015] In some embodiments, the thickness of the functional layer is 0.1 μm to 4 μm, and optionally 0.5 μm to 3 μm; and / or the coating weight of the functional layer is 1 g / m 2 Up to 3g / m 2When the thickness of the functional layer is within the above range, the mechanical properties of the separator as a whole can be improved. When the coating weight of the functional layer is within the above range, the mechanical properties of the separator as a whole can be improved.
[0016] In some embodiments, the thickness of the substrate is less than or equal to 16 μm, and can be 5 μm to 14 μm. The functional layer of the embodiment of the present application is conducive to improving the overall mechanical properties of the separator, so that a thinner substrate can be selected, thereby helping to improve the energy density of the battery cell.
[0017] In a second aspect, an embodiment of the present application further proposes a composite material, which includes a metal-organic framework compound and a chelate connected to each other, wherein the metal-organic framework compound is formed by coordination of metal ions and organic ligands, the valence of the metal ions is greater than or equal to divalence, and the organic ligands include polycarboxylic acid groups.
[0018] In some embodiments, the valence of the metal ion is greater than or equal to tetravalence; alternatively, the valence of the metal ion is greater than or equal to pentavalence; further alternatively, the valence of the metal ion is greater than or equal to hexavalence. As the valence of the metal ion increases, the number of connection sites that the metal ion can provide increases, that is, the number of organic ligands coordinated to the metal ion increases, which is conducive to the formation of a metal organic framework compound with a smaller pore size, and is conducive to the metal organic framework compound adsorbing metal impurity ions through the pore size effect.
[0019] In some embodiments, the metal ions may include Zr 2+ 、Zr 3+ 、Zr 4+ 、Bi 3+ 、Bi 5+ 、Zn 2+ , Hf 4+ 、Co 2+ 、Co 3+ , Mn 4+ , Mn 5+ and Mn 6+ At least one of; Optionally, the metal ion may include Zr 3+ 、Zr 4+ 、Bi 3+ 、Bi 5+ , Hf 4+ 、Co 3+ , Mn 4+ , Mn 5+ and Mn 6+ At least one of; further optionally, the metal ions may include Zr 4+ 、Bi 5+ , Hf 4+ , Mn 4+ , Mn5+ and Mn 6+ At least one of; Further optionally, the metal ions may include Bi 5+ , Mn 5+ and Mn 6+ At least one of; Further optionally, the metal ions may include Mn 6+ .
[0020] In some embodiments, the organic ligand includes at least one of phthalic acid, terephthalic acid, 1,4-cyclohexanedicarboxylic acid, isophthalic acid, 4,4'-sulfonyl dibenzoic acid and 4,4'-dicarboxyl diphenyl ether. The above materials can exist stably for a long time in organic solvents, and because they all have a polycarboxylic acid structure, they are conducive to combining with chelates to improve the structural stability of the composite material.
[0021] In some embodiments, the chelate includes at least one of a carboxylic acid group, a phosphonic acid group and octanoyl hydroxamic acid; optionally, the chelate containing the carboxylic acid group includes at least one of ethylenediaminetetraacetic acid, aminotriacetic acid, diethylenetriaminepentaacetic acid and diethylenetriaminepentatriacetic acid; optionally, the chelate containing the phosphonic acid group includes one or more of hydroxyethylidene-1,1-diphosphonic acid, aminotrimethylenephosphonic acid, diethylenetriaminepentamethylenephosphonic acid, triethylenetetraaminehexamethylenphosphonic acid, bis(1,6-hexyl)triaminepentamethylenephosphonic acid and polyaminopolyethertetramethylenphosphonic acid. The coordination effect between the above chelate and the metal impurity ions is stronger, which is conducive to stabilizing the metal impurity ions in the isolation membrane. Moreover, the above chelate has good compatibility with the organic solvent in the electrolyte, which can improve the wetting performance of the electrolyte on the isolation membrane.
[0022] In some embodiments, the volume average particle size Dv50 of the composite material is 100 nm to 300 nm; and / or the average pore size of the composite material is 0.50 nm to 1.10 nm. When the average pore size of the composite material is within the above range, the average pore size of the composite material is relatively small, which is conducive to the composite material to play the role of pore size and adsorb metal impurity ions in the pore structure of the composite material.
[0023] In some embodiments, based on the mass of the composite material, the ratio of the mass percentage of the chelate to the mass percentage of the metal organic framework compound is 0.01 to 0.10: 1. When the mass percentage ratio of the chelate to the metal organic framework compound is within the above range, the metal organic framework compound plays a major role in adsorbing metal impurity ions, and the chelate plays an auxiliary role in chelating metal impurity ions. The two work together to stabilize the metal impurity ions in the composite material, which can effectively reduce the content of metal impurity ions in the system.
[0024] In a third aspect, an embodiment of the present application further proposes a battery, wherein the battery includes an isolation membrane, wherein the isolation membrane is an isolation membrane as described in any embodiment of the first aspect of the present application, or the isolation membrane includes a substrate and a functional layer arranged on at least one side of the substrate, and the functional layer includes a composite material as described in any embodiment of the second aspect of the present application.
[0025] In a fourth aspect, an embodiment of the present application further proposes an electrical device, comprising a battery as described in any embodiment of the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.
[0027] Figure 1 It is a schematic diagram of an embodiment of a battery cell of the present application.
[0028] Figure 2 yes Figure 1 An exploded schematic diagram of an embodiment of a battery cell.
[0029] Figure 3 It is a schematic diagram of an embodiment of a battery module of the present application.
[0030] Figure 4 It is a schematic diagram of an embodiment of the battery pack of the present application.
[0031] Figure 5 yes Figure 4 An exploded schematic diagram of an embodiment of a battery pack is shown.
[0032] Figure 6 It is a schematic diagram of an embodiment of an electric device including the battery cell of the present application as a power source.
[0033] The drawings are not necessarily drawn to scale.
[0034] The following are the descriptions of the reference numerals:
[0035] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module;
[0036] 5. Battery cell; 51. Housing; 52. Electrode assembly;
[0037] 53. Cover plate;
[0038] 6. Electrical equipment. DETAILED DESCRIPTION
[0039] Hereinafter, the embodiments of the isolation membrane, battery cell, battery and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0040] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0041] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0042] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0043] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0044] The battery cell includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The separator is located between the positive electrode sheet and the negative electrode sheet to separate the positive electrode sheet and the negative electrode sheet. The positive electrode sheet includes a positive active material. The positive active material is a donor of active ions such as sodium ions and lithium ions provided by the battery cell. The negative electrode sheet is an acceptor of active ions, and the electrolyte provides a migration path for active ions between the positive electrode sheet and the negative electrode sheet. In the production process of battery cells, the positive electrode active material and / or the electrolyte will inevitably introduce metal impurity ions, for example, at least one of iron ions, copper ions, zinc ions, cadmium ions, chromium ions, manganese ions, cobalt ions, and nickel ions. This part of metal ions usually does not include active ions such as lithium ions, sodium ions, and potassium ions. During the charging process of the battery cell, the metal impurity ions in the positive electrode active material can dissolve in the electrolyte, and the content of the metal impurity ions in the electrolyte increases. The metal impurity ions have a lower reduction potential than the active ions. These metal impurity ions can be embedded in the negative electrode plate in preference to the active ions, reducing the position of the active ion embedding and reducing the reversible capacity of the battery cell; and the metal impurity ions may precipitate on the surface of the negative electrode plate to form metal dendrites. The growth of metal dendrites may pierce the isolation membrane of the battery cell, resulting in direct contact between the positive electrode plate and the negative electrode plate, causing a short circuit, thereby reducing the reliability of the battery cell, and the self-discharge rate of the battery cell is too fast, and the cycle performance of the battery cell is deteriorated.
[0045] In view of the above problems, the embodiment of the present application proposes an isolation membrane, which includes a composite material, the composite material includes a metal organic framework compound and a chelate connected to each other, the metal organic framework compound is formed by the coordination of metal ions and organic ligands, the valence of the metal ions is divalent or more, and the organic ligands include a polycarboxylic acid structure. When the isolation membrane is applied to a battery cell, the metal organic framework material can bind metal impurity ions through pore size and electrostatic synergy, and the chelate can further bind to the metal impurity ions through chelation, reducing the content of metal impurity ions in the electrolyte, thereby reducing the number of metal impurity ions migrating to the negative electrode plate, increasing the position of active ions embedded in the negative electrode plate, and improving the reversible capacity of the battery cell; and reducing the risk of metal impurity ions precipitating on the surface of the negative electrode plate to form metal dendrites, improving the reliability of the battery cell; thereby, the self-discharge rate of the battery cell can be reduced, and the cycle performance of the battery cell can be improved.
[0046] Isolation film
[0047] In the first aspect, an embodiment of the present application proposes an isolation membrane, which includes a substrate and a functional layer arranged on at least one side of the substrate, wherein the functional layer includes a composite material, the composite material includes a metal-organic framework compound and a chelate connected to each other, the metal-organic framework compound is formed by coordination of metal ions and organic ligands, the valence of the metal ions is divalent or above, and the organic ligands include polycarboxylic acid groups.
[0048] The substrate includes two surfaces facing each other along the thickness direction of the isolation film, and the functional layer can be arranged on either one of the two surfaces or on both surfaces.
[0049] The isolation membrane includes a substrate and a functional layer, and the functional layer is arranged on one of the two surfaces of the substrate. In this case, when the isolation membrane is applied to a battery cell, the substrate of the isolation membrane can be arranged closer to the positive electrode sheet relative to the functional layer, that is, the functional layer is located on the side of the substrate away from the positive electrode sheet; or the functional layer of the isolation membrane can be arranged closer to the positive electrode sheet relative to the substrate, that is, the substrate is located on the side of the functional layer away from the positive electrode sheet.
[0050] Metal-Organic Frameworks (MOFs) compounds are porous materials formed by self-assembly of metal ions and organic ligands through coordination bonds. The organic ligands include polycarboxylic acid groups. The polycarboxylic acids can serve as organic skeletons for connecting metal ions, so that the polycarboxylic acids and metal ions are alternately connected to form a three-dimensional network structure, making the coordination of organic ligands and metal ions more stable. The skeleton structure of the metal-organic framework compound formed is more stable, and the pore size of the three-dimensional network structure is small, for example, nanometer-scale, which can serve as a channel for adsorbing metal impurity ions. The electrostatic effect of the organic skeleton in the three-dimensional network structure can further adsorb metal impurity ions. The electrostatic effect has a stronger selectivity for high-valent metal impurity ions, and has a relatively small effect on the adsorption of low-valent active ions such as lithium ions and sodium ions.
[0051] Metal ions serve as the skeleton center of metal organic framework compounds and can provide active connection sites. The valence state of metal ions is relatively high, for example, above divalent, and the metal ions can provide relatively more connection sites, that is, the number of organic ligands coordinated to the metal ions is large, which is conducive to forming metal organic framework compounds with smaller pore sizes with organic ligands. The pore size enables metal impurity ions to enter the pore structure of the metal organic framework compound, so that the metal organic framework compound can adsorb metal impurity ions through pore size effect and electrostatic synergy, thereby reducing the number of metal impurity ions migrating to the negative electrode.
[0052] Since the ability of metal organic framework compounds to adsorb metal impurity ions is limited, after the metal impurity ions adsorbed by the metal organic framework compound reach saturation, the metal impurity ions have the risk of desorption, and the embodiment of the present application is also combined with a chelate on the skeleton structure of the metal organic framework compound, and the chelate is conducive to further chelating the metal impurity ions. Specifically, the polycarboxylic acid group has an active connection site, which is conducive to coordination connection with the chelate, and the chelate is composited on the skeleton structure of the metal organic framework compound; since the valence state of the metal ion is relatively high, the metal ion may also have an active site, so that the chelate can be coordinated and connected with the metal ion through the active site on the metal ion, so that the connection stability of the chelate and the skeleton structure of the metal organic framework compound is higher, and the structural stability of the composite material formed is higher. The chelate can combine with the metal impurity ions through coordination to form a chelate, stabilize the metal impurity ions in the chelate, further reduce the risk of the metal impurity ions migrating to the negative electrode, and alleviate the risk of the metal impurity ions precipitating on the surface of the negative electrode to form metal dendrites, thereby improving the reliability of the battery cell; it can also reduce the self-discharge rate of the battery cell and improve the cycle performance of the battery cell.
[0053] The valence of the metal ion can be divalent, trivalent, tetravalent, pentavalent, hexavalent, heptavalent or a range consisting of any two of the above valences. As the valence of the metal ion increases, the metal ion can provide more connection sites, that is, the number of organic ligands coordinated to the metal ion increases, which is conducive to the formation of a metal organic framework compound with a smaller pore size, and is conducive to the metal organic framework compound adsorbing metal impurity ions through the pore size effect.
[0054] In some embodiments, the valence of the metal ion is greater than or equal to trivalent; alternatively, the valence of the metal ion is greater than or equal to tetravalent; alternatively, the valence of the metal ion is greater than or equal to pentavalent; further alternatively, the valence of the metal ion is greater than or equal to hexavalent. When the valence of the metal ion is within the above range, it can provide more active connection sites, which is conducive to coordination and binding with organic ligands and chelates, and the structure of the formed composite material is more stable.
[0055] In some embodiments, the metal ions may include Zr 2+ 、Zr 3+ 、Zr 4+ 、Bi 3+ 、Bi 5+ 、Zn 2+ , Hf 4+ 、Co 2+ 、Co 3+ , Mn 4+ , Mn 5+ and Mn 6+ At least one of; Optionally, the metal ion may include Zr 3+ 、Zr 4+ 、Bi 3+ 、Bi 5+ , Hf 4+ 、Co 3+ , Mn 4+ , Mn 5+ and Mn 6+ At least one of; further optionally, the metal ions may include Zr 4+ 、Bi 5+ , Hf 4+ , Mn 4+ , Mn 5+ and Mn 6+ At least one of; Further optionally, the metal ions may include Bi 5+ , Mn 5+ and Mn 6+ At least one of; Further optionally, the metal ions may include Mn 6+ .
[0056] In some embodiments, the polycarboxylic acid group may include at least one of a dicarboxylic acid group, a tricarboxylic acid group, and a tetracarboxylic acid group; the polycarboxylic acid can be used as an organic skeleton for connecting metal ions, and the metal ions are alternately connected to form a three-dimensional network structure, which is conducive to forming a three-dimensional network structure with nanometer-level pores; however, as the number of carboxylic acids increases, the pore size structure is too small, which is not conducive to the adsorption of metal impurity ions. Therefore, optionally, the polycarboxylic acid group may include a dicarboxylic acid group. Dicarboxylic acids are more conducive to forming a symmetrical structure and improving the stability of the three-dimensional network structure.
[0057] For example, the organic ligand may include at least one of phthalic acid, terephthalic acid, 1,4-cyclohexanedicarboxylic acid, isophthalic acid, 4,4'-sulfonyl dibenzoic acid, and 4,4'-dicarboxyl diphenyl ether. The above materials can exist stably for a long time in organic solvents, and because they all have a polycarboxylic acid structure, they are conducive to combining with chelates and improving the structural stability of the composite material. The above organic ligand includes a dicarboxylic acid structure, which is conducive to the adsorption of metal impurity ions through pore size and electrostatic effects.
[0058] Exemplarily, the organic coordination agent may include 5-nitro-1,2,3-benzenetricarboxylic acid, 4,4'4"-triphenylamine tricarboxylate.
[0059] In some embodiments, the chelate may include at least one of a carboxylic acid group, a phosphonic acid group, and octanoyl hydroxamic acid. The coordination effect between the chelate and the metal impurity ions is stronger, which is conducive to stabilizing the metal impurity ions in the isolation membrane. In addition, the chelate has good compatibility with the organic solvent in the electrolyte, which can improve the wetting performance of the electrolyte on the isolation membrane.
[0060] Alternatively, the chelate containing a carboxylic acid group may include at least one of ethylenediaminetetraacetic acid, aminotriacetic acid, diethylenetriaminepentaacetic acid, and diethylenetriaminepentatriacetic acid.
[0061] Alternatively, the chelate containing phosphonic acid groups may include one or more of hydroxyethylene-1,1-diphosphonic acid, aminotrimethylenephosphonic acid, diethylenetriaminepentamethylenephosphonic acid, triethylenetetraaminehexamethylenephosphonic acid, bis(1,6-hexamethylene)triaminepentamethylenephosphonic acid, and polyaminopolyethertetramethylenephosphonic acid.
[0062] The metal organic framework compound is a nanomaterial with a relatively small particle size. The composite material formed by the combination of the metal organic framework compound and the chelate is also a nanomaterial with a relatively small particle size. When the composite material is arranged in a functional layer, the thickness of the functional layer can be made relatively small.
[0063] In some embodiments, the volume average particle size Dv50 of the composite material can be 100nm to 300nm. Exemplarily, the volume average particle size Dv50 of the composite material can be 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, 210nm, 220nm, 230nm, 240nm, 250nm, 260nm, 270nm, 280nm, 290nm, 300nm or a range consisting of any two of the above values.
[0064] In the embodiment of the present application, the volume average particle size Dv50 of the material has a well-known meaning in the art. The volume average particle size Dv50 of the material refers to the particle size corresponding to 50% in the volume distribution. It can be detected by using equipment and methods well-known in the art. A certain amount of the composite material is taken as a sample, and the volume average particle size Dv50 is tested by a Mastersizer2000E laser particle size analyzer according to the test standard GB / T 19077-2016.
[0065] In some embodiments, the average pore size of the composite material can be 0.50 nm to 1.10 nm. When the average pore size of the composite material is within the above range, the average pore size of the composite material is relatively small, which is conducive to the composite material playing the role of pore size and adsorbing metal impurity ions in the pore structure of the composite material.
[0066] Illustratively, the average pore size of the composite material can be 0.5 nm, 0.55 nm, 0.60 nm, 0.65 nm, 0.70 nm, 0.75 nm, 0.80 nm, 0.85 nm, 0.90 nm, 0.95 nm, 1.00 nm, 1.05 nm, 1.10 nm, or a range consisting of any two of the above values.
[0067] In the embodiments of the present application, the average pore size of the composite material has a well-known meaning in the art and can be detected using equipment and methods well-known in the art. A certain amount of the composite material is taken as a sample, and the average pore size is tested using a Tri-Star 3020 specific surface area pore size analyzer produced by Micromeritics, USA, in accordance with the test standard GB / T 19587-2017.
[0068] In some embodiments, based on the mass of the composite material, the ratio of the mass percentage of the chelate to the mass percentage of the metal organic framework compound is 0.01 to 0.10: 1. When the mass percentage ratio of the chelate to the metal organic framework compound is within the above range, the metal organic framework compound plays a major role in adsorbing metal impurity ions, and the chelate plays an auxiliary role in chelating metal impurity ions. The two work together to stabilize the metal impurity ions in the composite material, which can effectively reduce the content of metal impurity ions in the system.
[0069] Illustratively, the ratio of the mass percentage of the chelate to the mass percentage of the metal organic framework compound can be 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.10:1 or a range consisting of any two of the above values.
[0070] In some embodiments, based on the mass of the functional layer, the mass percentage of the composite material is 0.1% to 1.0%; when the mass percentage of the composite material is within the above range, the metal impurity ions in the battery monomer system can be effectively adsorbed and stabilized.
[0071] Illustratively, the mass percentage of the composite material may be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0% or a range consisting of any two of the above values.
[0072] In some embodiments, the functional layer may further include heat-resistant particles, and the heat-resistant particles may include inorganic particles.
[0073] In some embodiments, the mass percentage of inorganic particles in the functional layer is less than or equal to 50%, which can improve the heat resistance of the isolation film. Exemplarily, the mass percentage of inorganic particles in the functional layer is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or a range consisting of any two of the above values.
[0074] The inorganic particles may include at least one of inorganic particles having a dielectric constant of 5 or more, inorganic particles having the ability to transport active ions, and inorganic particles capable of electrochemical oxidation and reduction.
[0075] In some embodiments, the inorganic particles having a dielectric constant of 5 or more may include boehmite (γ-AlOOH), aluminum oxide (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), silicon oxide SiOx (0<x≤2), tin dioxide (SnO2), titanium oxide (TiO2), calcium oxide (CaO), zinc oxide (ZnO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), nickel oxide (NiO), hafnium dioxide (HfO2), cerium oxide (CeO2), zirconium titanate (ZrTiO3), barium titanate (BaTiO3), magnesium fluoride (MgF2), Pb(Zr,Ti)O3 (abbreviated as PZT), Pb 1-m La m Zr 1-n Ti n O3 (abbreviated as PLZT, 0<m<1, 0<n<1) and Pb(Mg3Nb 2 / 3 )O3-PbTiO3 (abbreviated as PMN-PT).
[0076] In some embodiments, the inorganic particles capable of transporting active ions may include lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0<x<2, 0<y<3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0<x<2, 0<y<1, 0<z<3), (LiAlTiP)xOy glass (0<x<4, 0<y<13), lanthanum lithium titanate (Li x La y TiO3, 0<x<2, 0<y<3), lithium germanium thiophosphate (Li x Ge y P z S w , 0<x<4, 0<y<1, 0<z<1, 0<w<5), lithium nitride (LixNy, 0<x<4, 0<y<2), SiS2 glass (Li x Si y S z , 0<x<3, 0<y<2, 0<z<4) and P2S5 type glass (Li x P y S z , 0<x<3, 0<y<3, 0<z<7).
[0077] In some embodiments, the inorganic particles capable of electrochemical oxidation and reduction may include at least one of lithium-containing transition metal oxides, olivine-structured lithium-containing phosphates, carbon-based materials, silicon-based materials, tin-based materials, and lithium-titanium compounds.
[0078] In some embodiments, the functional layer may further include a binder. As an example, the binder may include at least one of an aqueous solution type acrylic resin (e.g., acrylic acid, methacrylic acid, sodium acrylate monomer homopolymer or copolymer with other comonomers), polyvinyl alcohol (PVA), isobutylene-maleic anhydride copolymer, and polyacrylamide.
[0079] In some embodiments, the thickness of the functional layer may be 0.1 μm to 4 μm, optionally 0.5 μm to 3 μm. When the thickness of the functional layer is within the above range, the overall mechanical properties of the isolation film can be improved. In the present application, the thickness of the functional layer refers to the thickness of the functional layer located on one side of the substrate. Exemplarily, the thickness of the functional layer may be 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, or a range consisting of any two of the above values.
[0080] In some embodiments, the coating weight of the functional layer is 1 g / m 2 Up to 3g / m 2 The coating weight of the functional layer refers to the coating weight of the functional layer located on one side of the substrate. When the coating weight of the functional layer is within the above range, the overall mechanical properties of the separator can be improved.
[0081] In some embodiments, the thickness of the substrate may be less than or equal to 16 μm, and may be 5 μm to 14 μm. The functional layer of the embodiment of the present application is conducive to improving the mechanical properties of the isolation membrane as a whole, so that a thinner substrate can be selected, thereby helping to improve the energy density of the battery cell. Exemplarily, the thickness of the substrate can be 1 μm, 2 μm, 3 μm, 5 μm, 10 μm, 12 μm, 15 μm, 16 μm, or a range consisting of any two of the above values.
[0082] In some embodiments, the porosity of the substrate is greater than or equal to 25%. When the porosity of the substrate is within the above range, the air permeability of the substrate can be guaranteed to be conducive to the migration of active ions, and because the porosity is relatively small, the mechanical properties of the substrate can also be guaranteed, providing good support for the functional layer.
[0083] In some embodiments, the substrate may include at least one of a polyolefin-based polymer (e.g., at least one of polyethylene, polypropylene, and polyvinylidene fluoride), a porous glass fiber, and a porous nonwoven fabric. The substrate may be a single-layer film or a multi-layer composite film. When the substrate is a multi-layer composite film, the materials of each layer may be the same or different. The substrate formed by the above polymer has good chemical stability and mechanical stability.
[0084] It should be noted that the functional layer parameters and functional layer parameters (such as thickness, etc.) of the above-mentioned isolation membrane are all functional layer parameters on one side of the substrate and functional layer parameters on one side of the substrate. When the functional layer parameters are set on both sides of the substrate, the functional layer parameters on either side meet the requirements of this application and are considered to fall within the protection scope of this application. When the functional layer parameters are set on both sides of the substrate, the functional layer parameters on either side meet the requirements of this application and are considered to fall within the protection scope of this application.
[0085] Method for preparing isolation film
[0086] In a second aspect, an embodiment of the present application provides a method for preparing an isolation film, the method comprising:
[0087] Step S100, providing a metal organic framework compound, wherein the metal organic framework compound is formed by coordination of a metal ion and an organic ligand, the valence of the metal ion is greater than or equal to divalent, and the organic ligand includes a polyvalent carboxylic acid group;
[0088] Step S200, providing the chelate to the metal organic framework compound to prepare a composite material;
[0089] Step S300 , providing a composite material onto at least one surface of a base film to form a functional layer.
[0090] According to the method of the embodiment of the present application, an isolation membrane can be prepared simply.
[0091] In some embodiments, step S300 may include dispersing the composite material in a heat-resistant slurry, and coating the heat-resistant slurry on at least one surface of the base film to form a functional layer.
[0092] Composite Materials
[0093] In a third aspect, an embodiment of the present application proposes a composite material, which includes a metal-organic framework compound and a chelate connected to each other, wherein the metal-organic framework compound is formed by coordination of metal ions and organic ligands, wherein the valence of the metal ions is divalent or higher, and the organic ligands include polycarboxylic acid groups.
[0094] In some embodiments, in some embodiments, the valence of the metal ion is greater than or equal to trivalent; optionally, the valence of the metal ion is greater than or equal to tetravalent; optionally, the valence of the metal ion is greater than or equal to pentavalent; further optionally, the valence of the metal ion is greater than or equal to hexavalent.
[0095] In some embodiments, the metal ions may include Zr 2+ 、Zr 3+ 、Zr 4+ 、Bi 3+ 、Bi 5+ 、Zn 2+ , Hf 4+ 、Co 2+ 、Co 3+ , Mn 4+ , Mn 5+ and Mn 6+ At least one of; Optionally, the metal ion may include Zr 3+ 、Zr 4+ 、Bi 3+ 、Bi 5+ , Hf 4+ 、Co 3+ , Mn 4+ , Mn 5+ and Mn 6+ At least one of; further optionally, the metal ions may include Zr 4+ 、Bi 5+ , Hf 4+ , Mn 4+ , Mn 5+ and Mn 6+ At least one of; Further optionally, the metal ions may include Bi 5+ , Mn 5+ and Mn 6+ At least one of; Further optionally, the metal ions may include Mn 6+ .
[0096] In some embodiments, the polycarboxylic acid group may include at least one of a dicarboxylic acid group, a tricarboxylic acid group, and a tetracarboxylic acid group; alternatively, the polycarboxylic acid group may include a dicarboxylic acid group.
[0097] For example, the organic ligand may include at least one of phthalic acid, terephthalic acid, 1,4-cyclohexanedicarboxylic acid, isophthalic acid, 4,4'-sulfonyl dibenzoic acid, and 4,4'-dicarboxyl diphenyl ether. The above materials can exist stably for a long time in organic solvents, and because they all have a polycarboxylic acid structure, they are conducive to combining with chelates to improve the structural stability of the composite material.
[0098] Exemplarily, the organic coordination agent may include 5-nitro-1,2,3-benzenetricarboxylic acid, 4,4'4"-triphenylamine tricarboxylate.
[0099] In some embodiments, the chelate may include at least one of a carboxylic acid group, a phosphonic acid group, and octanoylhydroxamic acid.
[0100] Alternatively, the chelate containing a carboxylic acid group may include at least one of ethylenediaminetetraacetic acid, aminotriacetic acid, diethylenetriaminepentaacetic acid, and diethylenetriaminepentatriacetic acid.
[0101] Alternatively, the chelate containing phosphonic acid groups may include one or more of hydroxyethylene-1,1-diphosphonic acid, aminotrimethylenephosphonic acid, diethylenetriaminepentamethylenephosphonic acid, triethylenetetraaminehexamethylenephosphonic acid, bis(1,6-hexamethylene)triaminepentamethylenephosphonic acid, and polyaminopolyethertetramethylenephosphonic acid.
[0102] In some embodiments, the volume average particle size Dv50 of the composite material may be from 100 nm to 300 nm.
[0103] In some embodiments, the average pore size of the composite material may be between 0.50 nm and 1.10 nm.
[0104] In some embodiments, based on the mass of the composite material, the ratio of the mass percentage of the chelate to the mass percentage of the metal organic framework compound is 0.01 to 0.10:1.
[0105] Battery Cell
[0106] In a fourth aspect, an embodiment of the present application provides a battery cell, wherein the battery cell includes a separator. The separator may include a separator according to any embodiment of the first aspect of the present application or a separator prepared by a method according to any embodiment of the second aspect of the present application, and the separator serves to isolate the positive electrode sheet from the negative electrode sheet. By using the separator, the reliability, self-discharge performance, and cycle performance of the battery cell can be improved.
[0107] [Positive electrode]
[0108] In some embodiments, the battery cell further includes a positive electrode tab.
[0109] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material.
[0110] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two facing surfaces of the positive electrode current collector.
[0111] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0112] In some embodiments, the positive electrode active material may be a positive electrode active material for a battery cell known in the art. As an example, the positive electrode active material may include at least one of the following materials, a layered positive electrode active material (e.g., ternary, lithium nickelate / sodium, lithium cobaltate / sodium, lithium manganate / sodium, lithium-rich / sodium layered and rock salt phase layered materials), an olivine-type phosphate active material, a spinel structured positive electrode active material (e.g., spinel lithium manganate, spinel nickel lithium manganate, lithium-rich spinel lithium manganate, and lithium nickel lithium manganate, etc.).
[0113] For example, the general formula of the layered positive electrode active material is Li x A y Ni a Co b Mn c M (1-a-b-c) Y z , wherein 0≤x≤2.1, 0≤y≤2.1, and 0.9≤x+y≤2.1; 0≤a≤1, 0≤b≤1, 0≤c≤1, and 0.1≤a+b+c≤1; 1.8≤z≤3.5; A includes one or more of Na, K, and Mg; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; and Y includes one or more of O and F. Specifically, the layered positive electrode active material may include lithium cobalt oxide LCO, lithium nickel oxide LNO, lithium manganese oxide LMO, and the like.
[0114] Optionally, the layered positive electrode active material is a ternary material, for example, 0<a≤1, 0<b≤1, 0<c≤1, illustratively, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811) and LiNi 0.5 Co0.2 Mn 0.3 O2 (NCM523) or more.
[0115] For example, the general formula of the olivine phosphate active material is Li x A y Me a M b P 1-c X c Y z , wherein 0≤x≤1.3, 0≤y≤1.3, and 0.9≤x+y≤1.3; 0.9≤a≤1.5, 0≤b≤0.5, and 0.9≤a+b≤1.5; 0≤c≤0.5; 3≤z≤5; A includes one or more of Na, K, and Mg; Me includes one or more of Mn, Fe, Co, and Ni; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X includes one or more of S, Si, Cl, B, C, and N; and Y includes one or more of O and F. Specifically, the olivine-type phosphate active material includes one or more of LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.
[0116] For example, the general formula of the positive electrode active material of the spinel structure is Li x A y Mn a M 2-a Y z , wherein 0≤x≤2, 0≤y≤1, and 0.9≤x+y≤2; 0.5≤a≤2; 3≤z≤5; A includes one or more of Na, K, and Mg; M includes one or more of Ni, Co, B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; and Y includes one or more of O and F. Specifically, the positive active materials of the spinel structure include LiMn2O4, LiNi 0.5 Mn 1.5 O4、LiCr 0.3 Mn 1.7 O4、Li 1.1 Al 0.1 Mn 1.9 O4, Li2Mn2O4 and Li 1.5 One or more of Mn2O4.
[0117] The battery cell will be accompanied by the deintercalation and consumption of active ions such as Li during the charge and discharge process, and the molar content of Li in the battery cell is different when it is discharged to different states. In the list of positive electrode active materials in the embodiments of the present application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li may change after charge and discharge cycles.
[0118] In the list of positive electrode active materials in the embodiments of the present application, the molar content of oxygen O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen O to change. In reality, the molar content of oxygen O will fluctuate.
[0119] In some embodiments, the positive electrode active material layer may further include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0120] In some embodiments, the positive electrode active material layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0121] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0122] [Negative electrode]
[0123] In some embodiments, the battery cell further includes a negative electrode tab.
[0124] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0125] The negative electrode active material may be a negative electrode active material for a battery cell known in the art. As an example, the negative electrode active material may include but is not limited to at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy material. The tin-based material may include at least one of elemental tin, tin oxide, and tin alloy material.
[0126] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. The embodiment of the present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the negative electrode conductive agent is ≤5wt%.
[0127] In some embodiments, the negative electrode film layer may also optionally include a negative electrode binder. The embodiment of the present application has no particular restrictions on the type of the negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA) and carboxymethyl chitosan (CMCS). In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the negative electrode binder is ≤5wt%.
[0128] In some embodiments, the negative electrode film layer may further include other additives. As an example, other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC-Na), PTC thermistor materials, etc. In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the other additives is ≤2wt%.
[0129] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0130] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.
[0131] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate described in the embodiments of the present application further includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode collector and the negative electrode film layer and disposed on the surface of the negative electrode collector. In some other embodiments, the negative electrode plate described in the embodiments of the present application further includes a protective layer covering the surface of the negative electrode film layer.
[0132] [Electrolyte]
[0133] In some embodiments, the battery cell may further include an electrolyte.
[0134] During the charge and discharge process of the battery cell, active ions are embedded and released back and forth between the positive electrode and the negative electrode, and the electrolyte plays a role in conducting active ions between the positive electrode and the negative electrode. The embodiment of the present application has no particular limitation on the type of electrolyte, which can be selected according to actual needs.
[0135] The electrolyte solution includes an electrolyte salt and a solvent. The types of the electrolyte salt and the solvent are not specifically limited and can be selected according to actual needs.
[0136] When the battery cell of an embodiment of the present application is a lithium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0137] When the battery cell of an embodiment of the present application is a sodium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFOP) and sodium tetrafluorooxalatophosphate (NaTFOP).
[0138] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0139] In some embodiments, the electrolyte may further include additives, for example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature power performance, etc.
[0140] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly by a winding process and / or a lamination process.
[0141] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0142] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).
[0143] The present application has no particular restrictions on the shape of the battery cell, which can be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.
[0144] In some embodiments, Figure 2 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process and / or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.
[0145] The preparation method of the battery cell of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, the separator and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying, and the battery cell is obtained through vacuum packaging, standing, forming, shaping and other processes.
[0146] In some embodiments of the present application, the battery cells according to the present application may be assembled into a battery module. The battery module may contain multiple battery cells, and the specific number may be adjusted according to the application and capacity of the battery module.
[0147] Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3 As shown, in the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0148] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0149] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0150] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5As shown, the battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0151] The battery according to the embodiment of the present application may include one battery cell or a plurality of battery cells. When the battery includes a plurality of battery cells, the battery may include a battery module or a battery pack.
[0152] Electrical devices
[0153] The fifth aspect of the embodiment of the present application provides an electric device, which includes at least one of the battery cells, battery modules or battery packs of the present application. The battery cells, battery modules or battery packs can be used as the power source of the electric device, and can also be used as the energy storage unit of the electric device. The electric device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0154] The electrical device may select a battery cell, a battery module or a battery pack according to its usage requirements.
[0155] Figure 6 Schematic diagram of an exemplary electric device 6. The electric device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device 6 for high power and high energy density, a battery pack or a battery module may be used.
[0156] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.
[0157] Example
[0158] The following embodiments describe the contents disclosed in the present application in more detail, and these embodiments are only used for illustrative explanations, because it is obvious to those skilled in the art that various modifications and changes are made within the scope of the present application disclosure. Unless otherwise stated, all parts, percentages and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized according to conventional methods, and can be used directly without further processing, and the instruments used in the embodiments are commercially available.
[0159] Preparation of Lithium Ion Batteries in Examples and Comparative Examples
[0160] 1. Preparation of positive electrode sheet
[0161] Aluminum foil with a thickness of 12 μm was used as the positive electrode current collector.
[0162] The positive electrode active material LiNi 0.5 Co 0.2 Mn 0.3 O2, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in a proper amount of solvent N-methylpyrrolidone NMP at a weight ratio of 97.5:1.4:1.1 to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the surface of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained.
[0163] 2. Preparation of negative electrode sheet
[0164] A copper foil with a thickness of 8 μm was used as the negative electrode current collector.
[0165] The negative electrode active material artificial graphite, the binder styrene-butadiene rubber (SBR), the thickener sodium carboxymethyl cellulose (CMC-Na), and the conductive agent carbon black (Super P) are fully stirred and mixed in an appropriate amount of solvent deionized water at a weight ratio of 96.2:1.8:1.2:0.8 to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet is obtained.
[0166] 3. Isolation film
[0167] (1) Preparation of Metal-Organic Framework Compounds (MOFs)
[0168] The material containing metal ions and the organic ligand are mixed, and then N,N-dimethylformamide is added to the system, stirred to dissolve, transferred to the inner lining of a polytetrafluoroethylene reactor, and then transferred to an oven for reaction. The above reactants are then centrifuged and soaked in N,N-dimethylformamide, repeated 5 times, and then soaked in ethanol for 8 hours, centrifuged 4 times, and vacuum dried at 60°C for 6 hours to obtain metal organic framework compounds MOFs formed with metal ions as metal centers and organic ligands.
[0169] (2) Chelating metal organic frameworks
[0170] Weigh the chelate and the metal organic framework compound MOFs synthesized in the first step, weigh 500 mL of N,N-dimethylformamide as a solvent, add them to the microchannel reactor for continuous synthesis according to the preset reaction mass ratio of 1:100, the reaction time is 5 minutes, the temperature is 45°C, and a composite material is obtained.
[0171] (3) Preparation of isolation membrane
[0172] Weigh 2g of the composite material and add it to 500g of CCS slurry (alumina aqueous solution with a solid content of 45%), stir evenly, and evenly coat the CCS slurry containing the composite material on polypropylene PP (thickness of 12μm) to form a functional layer to obtain an isolation film. The coating weight of the functional layer is 2±0.1g / m 2 .
[0173] 4. Preparation of electrolyte
[0174] In an environment where the water content is less than 10 ppm, organic solvents ethylene carbonate EC and diethyl carbonate DMC are mixed in a volume ratio of 1:1 to obtain an electrolyte solvent, and then lithium salt and the mixed solvent are mixed to prepare an electrolyte with a lithium salt concentration of 1 mol / L.
[0175] 5. Preparation of battery cells
[0176] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then they are wound to obtain an electrode assembly; the electrode assembly is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0177] Example 1
[0178] The lithium ion battery is prepared by the above steps, wherein the preparation steps of the isolation membrane in Example 1 are as follows:
[0179] (1) Preparation of Metal-Organic Framework Compounds (MOFs)
[0180] 100 g of zirconium chloride and 60 g of 1,4-cyclohexanedicarboxylic acid were mixed, and then 45 g of N,N-dimethylformamide was added to the system, stirred and dissolved, transferred to a polytetrafluoroethylene reactor liner, and then transferred to an oven, reacted at 125°C for 15 hours, then the above reactants were centrifuged, and then soaked in 30 g of N,N-dimethylformamide for 6 hours, repeated 5 times, and then soaked in 20 g of ethanol for 8 hours, centrifuged 4 times, and vacuum dried at 60°C for 6 hours to obtain zirconium ion (Zr 4+ ) as the metal center and 1,4-cyclohexanedicarboxylic acid as the organic ligand.
[0181] (2) Chelating metal organic frameworks
[0182] Weigh 0.1 g of octanoylhydroxamic acid and 10 g of the metal organic framework compound MOFs synthesized in step (1), weigh 500 mL of N,N-dimethylformamide as a solvent, add them into a microchannel reactor according to a preset reaction mass ratio of 1:100 for continuous synthesis, the reaction time is 5 min, the temperature is 45°C, and a composite material is obtained.
[0183] (3) Preparation of isolation membrane
[0184] Weigh 2g of the composite material and add it to 500g of CCS slurry (alumina aqueous solution with a solid content of 45%), stir evenly, and evenly coat the CCS slurry containing the composite material on polypropylene PP (thickness of 12μm) to form a functional layer to obtain an isolation film. The coating weight of the functional layer is 2±0.1g / m 2 .
[0185] Comparative Example 1
[0186] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 is that the isolation film was prepared by the following steps:
[0187] The CCS slurry (solid content of 45% aluminum oxide aqueous solution) was uniformly coated on both surfaces of a polypropylene PP substrate (12 μm), and the CCS slurry was dried to form a functional layer to prepare a separator.
[0188] Comparative Example 2
[0189] A lithium ion battery is prepared by a method similar to that of Example 1. The difference from Example 1 is that the metal organic framework compound and the chelate of the isolation membrane are mixed in a physical mixing manner. The preparation steps include:
[0190] (1) Preparation of Metal-Organic Framework Compounds (MOFs)
[0191] 100 g of zirconium chloride and 60 g of 1,4-cyclohexanedicarboxylic acid were mixed, and then 45 g of N,N-dimethylformamide was added to the system, stirred and dissolved, transferred to a polytetrafluoroethylene reactor liner, and then transferred to an oven, reacted at 125°C for 15 hours, then the above reactants were centrifuged, and then soaked in 30 g of N,N-dimethylformamide for 6 hours, repeated 5 times, and then soaked in 20 g of ethanol for 8 hours, centrifuged 4 times, and vacuum dried at 60°C for 6 hours to obtain zirconium ion (Zr 4+ ) as the metal center and 1,4-cyclohexanedicarboxylic acid as the organic ligand.
[0192] (2) Chelating metal organic frameworks
[0193] Weigh 0.1 g of octanoylhydroxamic acid and 10 g of the metal organic framework compound MOFs synthesized in step (1) and mix them to prepare a composite material.
[0194] (3) Preparation of isolation membrane
[0195] Weigh 2 g of the composite material and add it to 500 g of CCS slurry (alumina aqueous solution with a solid content of 45%), stir evenly, and evenly coat the CCS slurry containing the composite material on polypropylene PP (thickness of 12 μm) to form a functional layer to prepare an isolation membrane.
[0196] Comparative Example 3
[0197] A lithium ion battery is prepared by a method similar to that of Example 1. The difference from Example 1 is that the isolation membrane only includes the metal organic framework compound and does not include the chelate. The steps of preparing the isolation membrane include:
[0198] (1) Preparation of Metal-Organic Framework Compounds (MOFs)
[0199] 100 g of zirconium chloride and 60 g of 1,4-cyclohexanedicarboxylic acid were mixed, and then 45 g of N,N-dimethylformamide was added to the system, stirred and dissolved, transferred to a polytetrafluoroethylene reactor liner, and then transferred to an oven, reacted at 125°C for 15 hours, then the above reactants were centrifuged, and then soaked in 30 g of N,N-dimethylformamide for 6 hours, repeated 5 times, and then soaked in 20 g of ethanol for 8 hours, centrifuged 4 times, and vacuum dried at 60°C for 6 hours to obtain zirconium ion (Zr 4+ ) as the metal center and metal-organic framework compounds MOFs with 1,4-cyclohexanedicarboxylic acid as organic ligands to prepare a composite material.
[0200] (2) Preparation of isolation membrane
[0201] Weigh 2 g of the composite material and add it to 500 g of CCS slurry (alumina aqueous solution with a solid content of 45%), stir evenly, and evenly coat the CCS slurry containing the composite material on polypropylene PP (thickness of 12 μm) to form a functional layer to prepare an isolation membrane.
[0202] Comparative Example 4
[0203] A lithium ion battery is prepared by a method similar to that of Example 1. The difference from Example 1 is that the isolation membrane only includes a chelate and does not include a metal organic framework compound. The steps of preparing the isolation membrane include:
[0204] Weigh 2 g of octanoylhydroxamic acid and add it to 500 g of CCS slurry (alumina aqueous solution with a solid content of 45%), stir evenly, and evenly coat the CCS slurry containing the composite material on polypropylene PP (thickness of 12 μm) to form a functional layer to prepare a separator.
[0205] Example 2
[0206] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the type of metal ions in the functional layer of the isolation membrane was adjusted.
[0207] In Example 2-1, the material containing metal ions is replaced by cobalt chloride instead of zirconium chloride.
[0208] In Example 2-2, the material containing metal ions is replaced by bismuth chloride instead of zirconium chloride.
[0209] In Example 2-3, the material containing metal ions is replaced by manganese chloride instead of zirconium chloride.
[0210] Example 3-1 and Example 3-2
[0211] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the type of organic ligand in the functional layer of the isolation membrane was adjusted.
[0212] Example 4-1 and Example 4-2
[0213] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the type of chelate in the substrate in the isolation membrane was adjusted.
[0214] Example 5-1 to Example 5-9
[0215] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the particle size of the composite material in the substrate in the isolation membrane was adjusted.
[0216] Example 5-1
[0217] (1) Preparation of Metal-Organic Framework Compounds (MOFs)
[0218] 100 g of zirconium chloride and 55 g of 1,4-cyclohexanedicarboxylic acid were mixed, and then 45 g of N,N-dimethylformamide was added to the system, stirred and dissolved, transferred to a polytetrafluoroethylene reactor liner, and then transferred to an oven, reacted at 125°C for 15 hours, then the above reactants were centrifuged, and then soaked in 30 g of N,N-dimethylformamide for 6 hours, repeated 5 times, and then soaked in 20 g of ethanol for 8 hours, centrifuged 4 times, and vacuum dried at 60°C for 6 hours to obtain zirconium ion (Zr 4+ ) as the metal center and 1,4-cyclohexanedicarboxylic acid as the organic ligand.
[0219] (2) Chelating metal organic frameworks
[0220] Weigh 0.1 g of octanoylhydroxamic acid and 10 g of the metal organic framework compound MOFs synthesized in the first step, weigh 500 mL of N,N-dimethylformamide as a solvent, add them into the microchannel reactor according to the preset reaction mass ratio of 1:100 for continuous synthesis, the reaction time is 5 min, the temperature is 45°C, and a composite material is obtained.
[0221] (3) Preparation of isolation membrane
[0222] Weigh 2 g of the composite material and add it to 500 g of CCS slurry (alumina aqueous solution with a solid content of 45%), stir evenly, and evenly coat the CCS slurry containing the composite material on polypropylene PP (thickness of 12 μm) to form a functional layer to prepare an isolation membrane.
[0223] Example 5-2
[0224] (1) Preparation of Metal-Organic Framework Compounds (MOFs)
[0225] 100 g of zirconium chloride and 49 g of 1,4-cyclohexanedicarboxylic acid were mixed, and then 45 g of N,N-dimethylformamide was added to the system, stirred to dissolve, transferred to a polytetrafluoroethylene reactor liner, and then transferred to an oven, reacted at 125°C for 15 hours, and then the above reactants were centrifuged and soaked in 30 g of N,N-dimethylformamide for 6 hours, repeated 5 times, and then soaked in 20 g of ethanol for 8 hours, centrifuged 4 times, and vacuum dried at 60°C for 6 hours to obtain a metal organic framework compound MOFs with zirconium ion (Zr4+) as the metal center and 1,4-cyclohexanedicarboxylic acid as the organic ligand.
[0226] (2) Chelating metal organic frameworks
[0227] Weigh 0.1 g of octanoylhydroxamic acid and 10 g of the metal organic framework compound MOFs synthesized in step (1), weigh 500 mL of N,N-dimethylformamide as a solvent, add them into a microchannel reactor according to a preset reaction mass ratio of 1:100 for continuous synthesis, the reaction time is 5 min, the temperature is 45°C, and a composite material is obtained.
[0228] (3) Preparation of isolation membrane
[0229] Weigh 2 g of the composite material and add it to 500 g of CCS slurry (alumina aqueous solution with a solid content of 45%), stir evenly, and evenly coat the CCS slurry containing the composite material on polypropylene PP (thickness of 12 μm) to form a functional layer to prepare an isolation membrane.
[0230] Example 5-3
[0231] (1) Preparation of Metal-Organic Framework Compounds (MOFs)
[0232] 100 g of zirconium chloride and 42 g of 1,4-cyclohexanedicarboxylic acid were mixed, and then 45 g of N,N-dimethylformamide was added to the system, stirred and dissolved, transferred to a polytetrafluoroethylene reactor liner, and then transferred to an oven, reacted at 125°C for 15 h, then the above reactants were centrifuged, and then soaked in 30 g of N,N-dimethylformamide for 6 h, repeated 5 times, and then soaked in 20 g of ethanol for 8 h, centrifuged 4 times, and vacuum dried at 60°C for 6 h to obtain zirconium ion (Zr 4+ ) as the metal center and 1,4-cyclohexanedicarboxylic acid as the organic ligand.
[0233] (2) Chelating metal organic frameworks
[0234] Weigh 0.1 g of octanoylhydroxamic acid and 10 g of the metal organic framework compound MOFs synthesized in step (1), weigh 500 mL of N,N-dimethylformamide as a solvent, add them into a microchannel reactor according to a preset reaction mass ratio of 1:100 for continuous synthesis, the reaction time is 5 min, the temperature is 45°C, and a composite material is obtained.
[0235] (3) Preparation of isolation membrane
[0236] Weigh 2 g of the composite material and add it to 500 g of CCS slurry (alumina aqueous solution with a solid content of 45%), stir evenly, and evenly coat the CCS slurry containing the composite material on polypropylene PP (thickness of 12 μm) to form a functional layer to prepare an isolation membrane.
[0237] Example 5-4
[0238] 100 g of zirconium chloride and 36 g of 1,4-cyclohexanedicarboxylic acid were mixed, and then 45 g of N,N-dimethylformamide was added to the system, stirred and dissolved, transferred to a polytetrafluoroethylene reactor liner, and then transferred to an oven, reacted at 125°C for 15 hours, then the above reactants were centrifuged, and then soaked in 30 g of N,N-dimethylformamide for 6 hours, repeated 5 times, and then soaked in 20 g of ethanol for 8 hours, centrifuged 4 times, and vacuum dried at 60°C for 6 hours to obtain zirconium ion (Zr 4+ ) as the metal center and 1,4-cyclohexanedicarboxylic acid as the organic ligand.
[0239] (2) Chelating metal organic frameworks
[0240] Weigh 0.1 g of octanoylhydroxamic acid and 10 g of the metal organic framework compound MOFs synthesized in step (1), weigh 500 mL of N,N-dimethylformamide as a solvent, add them into a microchannel reactor according to a preset reaction mass ratio of 1:100 for continuous synthesis, the reaction time is 5 min, the temperature is 45°C, and a composite material is obtained.
[0241] (3) Preparation of isolation membrane
[0242] Weigh 2 g of the composite material and add it to 500 g of CCS slurry (alumina aqueous solution with a solid content of 45%), stir evenly, and evenly coat the CCS slurry containing the composite material on polypropylene PP (thickness of 12 μm) to form a functional layer to prepare an isolation membrane.
[0243] Example 5-5
[0244] 100 g of zirconium chloride and 55 g of 1,4-cyclohexanedicarboxylic acid were mixed, and then 45 g of N,N-dimethylformamide was added to the system, stirred and dissolved, transferred to a polytetrafluoroethylene reactor liner, and then transferred to an oven, reacted at 125°C for 13 hours, and then the above reactants were centrifuged and then soaked in 30 g of N,N-dimethylformamide for 6 hours, repeated 5 times, and then soaked in 20 g of ethanol for 8 hours, centrifuged 4 times, and vacuum dried at 60°C for 6 hours to obtain zirconium ion (Zr 4+ ) as the metal center and 1,4-cyclohexanedicarboxylic acid as the organic ligand.
[0245] (2) Chelating metal organic frameworks
[0246] Weigh 0.1 g of octanoylhydroxamic acid and 10 g of the metal organic framework compound MOFs synthesized in step (1), weigh 500 mL of N,N-dimethylformamide as a solvent, add them into a microchannel reactor according to a preset reaction mass ratio of 1:100 for continuous synthesis, the reaction time is 5 min, the temperature is 45°C, and a composite material is obtained.
[0247] (3) Preparation of isolation membrane
[0248] Weigh 2 g of the composite material and add it to 500 g of CCS slurry (alumina aqueous solution with a solid content of 45%), stir evenly, and evenly coat the CCS slurry containing the composite material on polypropylene PP (thickness of 12 μm) to form a functional layer to prepare an isolation membrane.
[0249] Embodiment 5-6
[0250] 100 g of zirconium chloride and 55 g of 1,4-cyclohexanedicarboxylic acid were mixed, and then 45 g of N,N-dimethylformamide was added to the system, stirred and dissolved, transferred to a polytetrafluoroethylene reactor liner, and then transferred to an oven, reacted at 125°C for 11 hours, and then the above reactants were centrifuged and then soaked in 30 g of N,N-dimethylformamide for 6 hours, repeated 5 times, and then soaked in 20 g of ethanol for 8 hours, centrifuged 4 times, and vacuum dried at 60°C for 6 hours to obtain zirconium ion (Zr 4+) as the metal center and 1,4-cyclohexanedicarboxylic acid as the organic ligand.
[0251] (2) Chelating metal organic frameworks
[0252] Weigh 0.1 g of octanoylhydroxamic acid and 10 g of the metal organic framework compound MOFs synthesized in step (1), weigh 500 mL of N,N-dimethylformamide as a solvent, add them into a microchannel reactor according to a preset reaction mass ratio of 1:100 for continuous synthesis, the reaction time is 5 min, the temperature is 45°C, and a composite material is obtained.
[0253] (3) Preparation of isolation membrane
[0254] Weigh 2 g of the composite material and add it to 500 g of CCS slurry (alumina aqueous solution with a solid content of 45%), stir evenly, and evenly coat the CCS slurry containing the composite material on polypropylene PP (thickness of 12 μm) to form a functional layer to prepare an isolation membrane.
[0255] Embodiment 5-7
[0256] 100 g of zirconium chloride and 39 g of 1,4-cyclohexanedicarboxylic acid were mixed, and then 45 g of N,N-dimethylformamide was added to the system, stirred and dissolved, transferred to a polytetrafluoroethylene reactor liner, and then transferred to an oven, reacted at 125°C for 15 h, then the above reactants were centrifuged, and then soaked in 30 g of N,N-dimethylformamide for 6 h, repeated 5 times, and then soaked in 20 g of ethanol for 8 h, centrifuged 4 times, and vacuum dried at 60°C for 6 h to obtain zirconium ion (Zr 4+ ) as the metal center and 1,4-cyclohexanedicarboxylic acid as the organic ligand.
[0257] (2) Chelating metal organic frameworks
[0258] Weigh 0.1 g of octanoylhydroxamic acid and 10 g of the metal organic framework compound MOFs synthesized in step (1), weigh 500 mL of N,N-dimethylformamide as a solvent, add them into a microchannel reactor according to a preset reaction mass ratio of 1:100 for continuous synthesis, the reaction time is 5 min, the temperature is 45°C, and a composite material is obtained.
[0259] (3) Preparation of isolation membrane
[0260] Weigh 2 g of the composite material and add it to 500 g of CCS slurry (alumina aqueous solution with a solid content of 45%), stir evenly, and evenly coat the CCS slurry containing the composite material on polypropylene PP (thickness of 12 μm) to form a functional layer to prepare an isolation membrane.
[0261] Embodiment 5-8
[0262] 100 g of zirconium chloride and 55 g of 1,4-cyclohexanedicarboxylic acid were mixed, and then 45 g of N,N-dimethylformamide was added to the system, stirred and dissolved, transferred to a polytetrafluoroethylene reactor liner, and then transferred to an oven, reacted at 125°C for 11 hours, and then the above reactants were centrifuged and then soaked in 30 g of N,N-dimethylformamide for 6 hours, repeated 5 times, and then soaked in 20 g of ethanol for 8 hours, centrifuged 4 times, and vacuum dried at 60°C for 6 hours to obtain zirconium ion (Zr 4+ ) as the metal center and 1,4-cyclohexanedicarboxylic acid as the organic ligand.
[0263] (2) Chelating metal organic frameworks
[0264] Weigh 0.1 g of octanoylhydroxamic acid and 10 g of the metal organic framework compound MOFs synthesized in step (1), weigh 500 mL of N,N-dimethylformamide as a solvent, add them into a microchannel reactor according to a preset reaction mass ratio of 1:100 for continuous synthesis, the reaction time is 5 min, the temperature is 45°C, and a composite material is obtained.
[0265] (3) Preparation of isolation membrane
[0266] Weigh 2 g of the composite material and add it to 500 g of CCS slurry (alumina aqueous solution with a solid content of 45%), stir evenly, and evenly coat the CCS slurry containing the composite material on polypropylene PP (thickness of 12 μm) to form a functional layer to prepare an isolation membrane.
[0267] Embodiment 5-9
[0268] 100 g of zirconium chloride and 55 g of 1,4-cyclohexanedicarboxylic acid were mixed, and then 45 g of N,N-dimethylformamide was added to the system, stirred and dissolved, transferred to a polytetrafluoroethylene reactor liner, and then transferred to an oven, reacted at 125°C for 10 h, then the above reactants were centrifuged, and then soaked in 30 g of N,N-dimethylformamide for 6 h, repeated 5 times, and then soaked in 20 g of ethanol for 8 h, centrifuged 4 times, and vacuum dried at 60°C for 6 h to obtain zirconium ion (Zr 4+ ) as the metal center and 1,4-cyclohexanedicarboxylic acid as the organic ligand.
[0269] (2) Chelating metal organic frameworks
[0270] Weigh 0.1 g of octanoylhydroxamic acid and 10 g of the metal organic framework compound MOFs synthesized in step (1), weigh 500 mL of N,N-dimethylformamide as a solvent, add them into a microchannel reactor according to a preset reaction mass ratio of 1:100 for continuous synthesis, the reaction time is 5 min, the temperature is 45°C, and a composite material is obtained.
[0271] (3) Preparation of isolation membrane
[0272] Weigh 2 g of the composite material and add it to 500 g of CCS slurry (alumina aqueous solution with a solid content of 45%), stir evenly, and evenly coat the CCS slurry containing the composite material on polypropylene PP (thickness of 12 μm) to form a functional layer to prepare an isolation membrane.
[0273] Example 6-1 to Example 6-4
[0274] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the mass ratio of the chelate and the MOFs in the substrate in the isolation membrane was adjusted.
[0275] Example 7-1 to Example 7-4
[0276] A lithium ion battery was prepared by a method similar to that of Example 1, except that the mass content of the composite material in the isolation membrane was adjusted.
[0277] Example 8-1 and Example 8-2
[0278] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the coating weight of the functional layer in the isolation film was adjusted.
[0279] The relevant parameters of the embodiments and comparative examples are shown in Table 1.
[0280] Test Section
[0281] 1. Cycle performance test of lithium-ion batteries
[0282] At 25°C, the lithium-ion battery is charged to 4.25V at 2C constant current, then charged to 0.05C at 4.25V constant voltage, and then discharged to 2.8V at 1C constant current. This is a charge and discharge cycle. Taking the capacity of the first discharge as 100%, calculate the capacity retention rate of the battery after 500 cycles. The capacity retention rate of the battery after 500 cycles (%) = discharge capacity of the 500th cycle / capacity of the first discharge × 100%.
[0283] 2. K value test
[0284] The K value can be used to describe the physical quantity of the self-discharge rate of a battery cell. It can be calculated by dividing the open circuit voltage difference between two tests by the time interval △t between the two voltage tests. The formula is: K = (OCV2-OCV1) / △t. That is, K can represent the voltage drop per unit time. Generally speaking, the larger the K value, the faster the open circuit voltage drops or the larger the amplitude is, and there may be a micro-short circuit in the battery cell.
[0285] 3. ICP test of metal ion content in electrolyte
[0286] ICP instrument model: ICAP 7200ICP-OES, manufactured by ThermoFisher Technology (formerly Thermo Fisher Scientific);
[0287] Test conditions: The sample must be an electrolyte liquid. If it contains solid particles, it needs to be digested with acid or filtered to remove the solid particles. The range of the measured elements must be within the range of the standard curve. If it exceeds the range, the sample needs to be diluted.
[0288] Main operating procedures: 1. Test standard curve; 2. Dilute the sample to be tested; 3. Test the diluted sample; 4. Calculate and process the data to obtain the concentration of the element to be tested.
[0289] The electrolyte in a fresh battery cell is taken as a sample and tested by an inductively coupled plasma spectrometer ICP. A fresh battery cell refers to a battery cell that has been cycled less than 10 times.
[0290] Test Results
[0291] The test results are shown in Table 1.
[0292] Table 1
[0293]
[0294]
[0295] In Table 1, the K value represents the K value obtained by testing at a time interval of 14 days.
[0296] As can be seen from Table 1, compared with Comparative Example 1, Comparative Example 3 adds MOFs material to the isolation membrane, which can play a role in reducing metal impurity ions, but the effect of reducing metal impurity ions is relatively small. Comparative Example 4 adds a chelating agent to the isolation membrane, which can play a role in reducing metal impurity ions, but the effect of reducing metal impurity ions is relatively small. Comparative Example 2 adds MOFs material and chelating agent to the isolation membrane, which can play a role in reducing metal impurity ions, but the two act independently, and the effect of reducing metal impurity ions is relatively small.
[0297] The isolation membrane of the embodiment of the present application includes a composite material, and the composite material includes a metal organic framework compound and a chelate connected to each other, and the metal organic framework compound is formed by the coordination of metal ions and organic ligands, the valence of the metal ions is divalent or more, and the organic ligands include a polycarboxylic acid structure. The metal organic framework material can bind metal impurity ions through pore size and electrostatic synergy, and the chelate can further bind to the metal impurity ions through chelation, reducing the content of metal impurity ions in the electrolyte, thereby reducing the number of metal impurity ions migrating to the negative electrode plate, increasing the position of active ions embedded in the negative electrode plate, and improving the reversible capacity of the battery cell; and reducing the risk of metal impurity ions precipitating on the surface of the negative electrode plate to form metal dendrites, improving the reliability of the battery cell; thereby, the self-discharge rate of the battery cell can be reduced, and the cycle performance of the battery cell can be improved.
[0298] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.
Claims
1. An isolation membrane, comprising a substrate and a functional layer arranged on at least one side of the substrate, wherein the functional layer comprises a composite material, wherein the composite material comprises a metal organic framework compound and a chelate connected to each other, wherein the metal organic framework compound is formed by coordination of metal ions and organic ligands, wherein the valence of the metal ions is greater than or equal to divalence, and the organic ligands comprise polycarboxylic acid groups.
2. The isolation film according to claim 1, wherein: The valence of the metal ion is greater than or equal to tetravalent; optionally, the valence of the metal ion is greater than or equal to pentavalent; further optionally, the valence of the metal ion is greater than or equal to hexavalent.
3. The isolation film according to claim 1 or 2, wherein: The metal ions include Zr 2+ 、Zr 3+ 、Zr 4+ 、Bi 3+ 、Bi 5+ 、Zn 2+ , Hf 4+ 、Co 2+ 、Co 3+ , Mn 4+ , Mn 5+ and Mn 6+ At least one of; Optionally, the metal ions include Zr 4+ 、Bi 5+ , Hf 4+ , Mn 4+ , Mn 5+ and Mn 6+ At least one of; Further optionally, the metal ions include Bi 5+ , Mn 5+ and Mn 6+ At least one of .
4. The separator according to any one of claims 1 to 3, wherein: The organic ligand includes at least one of phthalic acid, terephthalic acid, 1,4-cyclohexanedicarboxylic acid, isophthalic acid, 4,4'-sulfonyldibenzoic acid and 4,4'-dicarboxy diphenyl ether.
5. The separator according to any one of claims 1 to 4, wherein: The chelate comprises at least one of a carboxylic acid group, a phosphonic acid group and octanoylhydroxamic acid; Optionally, the chelate comprising the carboxylic acid group comprises at least one of ethylenediaminetetraacetic acid, aminotriacetic acid, diethylenetriaminepentaacetic acid and diethylenetriaminepentatriacetic acid; Optionally, the chelate containing the phosphonic acid group includes one or more of hydroxyethylene-1,1-diphosphonic acid, aminotrimethylenephosphonic acid, diethylenetriaminepentamethylenephosphonic acid, triethylenetetraaminehexamethylenephosphonic acid, bis(1,6-hexamethylene)triaminepentamethylenephosphonic acid and polyaminopolyethertetramethylenephosphonic acid.
6. The separator according to any one of claims 1 to 5, wherein: The composite material has a volume average particle size Dv50 of 100 nm to 300 nm; and / or The average pore size of the composite material is 0.50 nm to 1.10 nm.
7. The separator according to any one of claims 1 to 6, wherein: Based on the mass of the composite material, the ratio of the mass percentage of the chelate to the mass percentage of the metal organic framework compound is 0.01 to 0.10:
1.
8. The separator according to any one of claims 1 to 7, wherein: Based on the mass of the functional layer, the mass percentage of the composite material is 0.1% to 1.0%.
9. The separator according to any one of claims 1 to 8, wherein: The functional layer also includes heat-resistant particles; Optionally, the mass percentage of the heat-resistant particles in the functional layer is less than or equal to 30%.
10. The separator according to any one of claims 1 to 9, wherein: The thickness of the functional layer is 0.1 μm to 4 μm, and optionally 0.5 μm to 3 μm; and / or The coating weight of the functional layer is 1 g / m 2 Up to 3g / m 2 .
11. The separator according to any one of claims 1 to 10, wherein: The thickness of the substrate is less than or equal to 16 μm, and can be 5 μm to 14 μm.
12. A composite material comprising a metal organic framework compound and a chelate connected to each other, wherein the metal organic framework compound is formed by coordination of metal ions and organic ligands, the valence of the metal ions is greater than or equal to divalence, and the organic ligands include polycarboxylic acid groups.
13. The composite material according to claim 12, wherein: The valence of the metal ion is greater than or equal to tetravalent; optionally, the valence of the metal ion is greater than or equal to pentavalent; further optionally, the valence of the metal ion is greater than or equal to hexavalent.
14. The composite material according to claim 12 or 13, wherein: The metal ions include Zr 2+ 、Zr 3+ 、Zr 4+ 、Bi 3+ 、Bi 5+ 、Zn 2+ , Hf 4+ 、Co 2+ 、Co 3+ , Mn 4+ , Mn 5+ and Mn 6+ At least one of; Optionally, the metal ions include Zr 4+ 、Bi 5+ , Hf 4+ , Mn 4+ , Mn 5+ and Mn 6+ At least one of; Further optionally, the metal ions include Bi 5+ , Mn 5+ and Mn 6+ At least one of .
15. The composite material according to any one of claims 12 to 14, wherein The organic ligand includes at least one of phthalic acid, terephthalic acid, 1,4-cyclohexanedicarboxylic acid, isophthalic acid, 4,4'-sulfonyldibenzoic acid and 4,4'-dicarboxy diphenyl ether.
16. The composite material according to any one of claims 12 to 15, wherein The chelate comprises at least one of a carboxylic acid group, a phosphonic acid group and octanoylhydroxamic acid; Optionally, the chelate comprising the carboxylic acid group comprises at least one of ethylenediaminetetraacetic acid, aminotriacetic acid, diethylenetriaminepentaacetic acid and diethylenetriaminepentatriacetic acid; Optionally, the chelate containing the phosphonic acid group includes one or more of hydroxyethylene-1,1-diphosphonic acid, aminotrimethylenephosphonic acid, diethylenetriaminepentamethylenephosphonic acid, triethylenetetraaminehexamethylenephosphonic acid, bis(1,6-hexamethylene)triaminepentamethylenephosphonic acid and polyaminopolyethertetramethylenephosphonic acid.
17. The composite material according to any one of claims 12 to 16, wherein The composite material has a volume average particle size Dv50 of 100 nm to 300 nm; and / or The average pore size of the composite material is 0.50 nm to 1.10 nm.
18. The composite material according to any one of claims 12 to 17, wherein Based on the mass of the composite material, the ratio of the mass percentage of the chelate to the mass percentage of the metal organic framework compound is 0.01 to 0.10:
1.
19. A battery, comprising an isolation membrane, wherein the isolation membrane is the isolation membrane as claimed in any one of claims 1 to 11; or the isolation membrane comprises a substrate and a functional layer arranged on at least one side of the substrate, wherein the functional layer comprises the composite material as claimed in any one of claims 12 to 18.
20. An electrical device comprising the battery according to claim 19.
Citation Information
Patent Citations
Synthesis method and application of organometallic framework compound with chemical formula of [C8H6Mn2O12]n
CN105399616A
Novel metal-organic framework material and preparing method and usage thereof
CN107159128A
Iron-containing chelating agent embedded MOF material as well as synthesis method and application thereof
CN112387251A
Metal-organic-framework (MOF) coated composite separators for electrochemical devices and applications of same
CN113574731A
Metal-organic framework composite diaphragm, battery comprising same and manufacturing method of metal-organic framework composite diaphragm
CN115810867A
Cited By
Coordination polymer nanowire diaphragm material, preparation method and application in field of sodium ion battery
CN119852642A